2018
DOI: 10.1002/pssb.201800114
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Centrosymmetric Superconductors on Honeycomb Lattice

Abstract: Non-centrosymmetric topological superconductivity is studied in correlated doped quantum spin-Hall insulators (QSHI) on honeycomb lattice without inversion symmetry where the intrinsic (Kane-Mele) and Rashba spin-orbit couplings can in general exist. The generic topologically non-trivial superconducting phase diagram of the model system is explored. Over a certain parameter range, the parity-mixing superconducting state with co-existing spin-singlet d þ id and spin-triplet p þ ip-wave pairing is found. On a zi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
(137 reference statements)
1
3
0
Order By: Relevance
“…CN = ±6, ±5, ±4, ±3, ±2, ±1) appearing and the TSC phase regions with CNs = 3 and −2 start to shrink when p A1 is greater than 0.14. The CN displays a sensitive dependence on V z and µ and distributes irregularly between CN = 3 and CN = −2 phases due to long-range pairing, which has also been observed in previous studies [19,20,22,24,[26][27][28][29]. It is notably that the sensitive non-zero CNs appear even under V z = 0 when p A1 is greater than or equal to 0.16 (see figures 2(c)-(f), 3 and 4), suggesting that there may be more intrinsic superconductors (e.g.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…CN = ±6, ±5, ±4, ±3, ±2, ±1) appearing and the TSC phase regions with CNs = 3 and −2 start to shrink when p A1 is greater than 0.14. The CN displays a sensitive dependence on V z and µ and distributes irregularly between CN = 3 and CN = −2 phases due to long-range pairing, which has also been observed in previous studies [19,20,22,24,[26][27][28][29]. It is notably that the sensitive non-zero CNs appear even under V z = 0 when p A1 is greater than or equal to 0.16 (see figures 2(c)-(f), 3 and 4), suggesting that there may be more intrinsic superconductors (e.g.…”
Section: Resultssupporting
confidence: 83%
“…However, recent research progress on topological materials has revealed the sensitivity and richness of the CN phase diagram to variations in the chemical potential (µ), magnetic field (V z ), and superconducting order parameter amplitude [19][20][21][22][23]. Furthermore, there is evidence of a mismatch between the CN and the number of TESs, indicating a deviation from the BBC principle [19,[21][22][23][24][25][26][27][28][29][30]. For example, 2 H b -stacked bilayer transition metal dichalcogenides and bilayer bismuth lattice considering on-site s-wave pairing with Kane-Mele type SOC strength 0.0075 eV or without SOC show the TSC phases with rich and high CNs up to 4 under various µ and superconducting order parameters, which do not strictly always contain the same number of TESs as the CNs [19,25,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly doped monolayer graphene has been proposed to exhibit these features, with unusual different properties [19][20][21][22]. For discussion and references on this topic, see [23,24].…”
Section: Introductionmentioning
confidence: 99%